Vitamin D: Role, Sources, Mechanism of Action and Significance for Human Health - Jusiak, Justyna; Halik, Paulina; Załęski , Daniel; Krankiewicz, Michał; Berdzińska, Martyna (Quality in Sport, 2025)
Introduction. Vitamin D is a key micronutrient regulating calcium–phosphate homeostasis, immune responses, and several extra-skeletal functions. Its active form, 1,25-dihydroxyvitamin D, acts via the vitamin D receptor present in numerous tissues. Materials and methods. A literature review was conducted using PubMed, Dove Press Medical, and Google Scholar. Studies concerning the sources, metabolism, mechanisms of action, and health effects of vitamin D were analyzed. Results. Vitamin D supports calcium absorption and bone mineralization, and supplementation of 800–1000 IU/day may reduce fracture risk in deficient individuals. It modulates innate and adaptive immunity by influencing cytokine production and the activity of T and B lymphocytes and macrophages. Deficiency is linked to increased susceptibility to infections, including tuberculosis and viral respiratory illnesses. Research also suggests associations between low vitamin D levels and autoimmune diseases, depression, and cancer, although intervention studies show inconsistent outcomes. Discussion. The reviewed evidence confirms the broad physiological effects of vitamin D; however, uncertainties remain regarding optimal dosage and its extra-skeletal benefits. Variability in clinical results may reflect differences in baseline 25(OH)D levels, study populations, and supplementation regimens. Conclusions. Vitamin D supplementation appears most beneficial for individuals with documented deficiency, whereas its preventive or therapeutic impact in the general population is less clear. Further high-quality studies are needed to establish optimal dosing and clarify its role in chronic and immune-related diseases.